European consensus‐based (S2k) Guideline on the Management of Herpes Zoster – guided by the European Dermatology Forum (EDF) in cooperation with the European Academy of Dermatology and Venereology (EADV), Part 1: Diagnosis. (2nd November 2016) - Werner, R.N.; Nikkels, A.F.; Marinović, B.; Schäfer, M.; Czarnecka‐Operacz, M.; Agius, A.M.; Bata‐Csörgő, Z.; Breuer, J.; Girolomoni, G.; Gross, G.E.; Langan, S.; Lapid‐Gortzak, R.; et al.
Abstract: Herpes zoster (HZ, shingles) is a frequent medical condition which may severely impact the quality of life of affected patients. Different therapeutic approaches to treat acute HZ are available. The aim of this European project was the elaboration of a consensus‐based guideline on the management of patients who present with HZ, considering different patient populations and different localizations. This interdisciplinary guideline aims at an improvement of the outcomes of the acute HZ management concerning disease duration, acute pain and quality of life of the affected patients and at a reduction of the incidence of postherpetic neuralgia and other complications. The guideline development followed a structured and predefined process, considering the quality criteria for guidelines development as suggested by the AGREE II instrument. The steering group was responsible for the planning and the organization of the guideline development process (Division of Evidence based Medicine, dEBM). The expert panel was nominated by virtue of clinical expertise and/or scientific experience and included experts from the fields of dermatology, virology/infectiology, ophthalmology, otolaryngology, neurology and anaesthesiology. Recommendations for clinical practice were formally consented during the consensus conference, explicitly considering different relevant aspects. The guideline was approved by the commissioning societies after an extensive internal and external review process. In this first part of the guideline, diagnostic means have been evaluated. The expert panel formally consented recommendations for the management of patients with (suspected) HZ, referring to the assessment of HZ patients, considering various specific clinical situations. Users of the guideline must carefully check whether the recommendations are appropriate for the context of intended application. In the setting of an international guideline, it is generally important to consider different national approaches and legal circumstances with regard to the regulatory approval, availability and reimbursement of diagnostic and therapeutic interventions.